العوامل الإجتماعية المؤدية الى إرتكاب الأحداث الجانحينن لجريمة السرقة من وجهة نظر الطاقم البيداغوجي - حميداتو, اسماء; سعداني, اسماء (جامعة الوادي university of Eloued, 2016)
هدفت هذه الدراسة إلى معرفة "العوامل الاجتماعٌة المؤدٌة لارتكاب الأحداث الجانحٌن لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً"، و لهذا تم صٌاغة التساؤل الرئٌسً كالتالً: "هل تؤدي بعض العوامل الاجتماعٌة إلى ارتكاب الأحداث الجانحٌن لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً؟" ، و تندرج تحت هذا التساؤل الرئٌسً تساؤلات فرعٌة نوردها كالتالً: - هل ٌؤدي المستوى الاقتصادي للأسرة إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً؟ - هل تؤدي التنشئة الاجتماعٌة الأسرٌة إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة الطاقم البٌداغوجً؟ - هل تؤدي الظروف السكنٌة الأسرٌة إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً؟ - هل ٌؤدي التفكك الأسري إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً؟ و قد تم الاعتماد على المنهج الوصفً لوصف الظاهرة المدروسة، و لجمع البٌانات من المٌدان استخدمنا أداة الاستبٌان، و ذلك لطبٌعة الموضوع، حٌث تضمن الاستبٌان 37سؤال مقسم إلى أربعة محاور، كل محور منها ٌجٌب على إحدى فرضٌات الدراسة، و قد كانت كل الأسئلة مغلقة. و قد تم إجراء الدراسة المٌدانٌة على 16مفردة من الطاقم البٌداغوج،ً من خلال الاعتماد على العٌنة القصدٌة، و كان ذلك بالمركز المختص بإعادة التربٌة بالوادي، و مصلحة الملاحظة و التربٌة فً الوسط المفتوح بقمار. و قد تم التوصل للنتائج التالٌة: - ٌؤدي المستوى الاقتصادي نسبٌا إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً. - تؤدي التنشئة الاجتماعٌة نسبٌا إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً. - تؤدي الظروف السكنٌة بشكل نسبً إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً. - ٌؤدي التفكك الأسري بشكل نسبً إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً. و علٌه فان:‌ب بعض العوامل الاجتماعٌة تؤدي نسبٌا إلى ارتكاب الأحداث لجرٌمة السرقة من وجهة نظر الطاقم البٌداغوجً. Abstruct study: the main point of this study is to know the social factors leading to the commission of the juvenile delinquents for the crime of the theft pedagogical a crew point of view and it has been drafting to a main question as: are some social factors lead to the commission to make a crime of theft from a pedagogical a crew point of view? Under this main question some sub-questions quote as follows: - is the economic level leads to the commission to make the crime of theft from pedagogical a crew point of view? -is socializing events leading to commit the crime of theft from a pedagogical crew? -are housing conditions lead the comission to make the crime of theft from pedagogical crew point of view? -are family distntegration leads to the commission to make the crime of theft from pedagogical a crew point of view? And it has been relying on decriptive approach to decribe the studied phenomon,andto collect data from field that we used survey tool and that for the nature of the subject,where the questionnaire included 37 questions divided into a four areas each axis of which answers one of the hypotheses study and all the questions have been closed. Intentionality on the sample and it was comptent to re-education in Eloud,and the survice of observation and education in the middle znd it has been field study preformed on 16 single pedagogical crew,by relying open on guemar and it has reached the following results:‌ج - Relatively economic level leads to the commission to make the crime of theft from the Pedagogical crew point of view -Relatively lead socializing event to commit the crime of theft the Pedagogical crew point of view Housing conditions relatively lead to the commission to make the crime of the theft the pedagogical crew point of view - Family disintegration relatively leads to the commission to make the crime of theft from the pedagogical crew point of view - And based on the answer to the sub-hypotheses (1,2,3,4) was the answer to the main question as follows: Some relatively social factors the commission to make the crime of theft from the pedagogical crew point of view
دراسة ميدانية على الطاقم البيداغوجي العامل بالمركز المختص لإعادةالتربية بالوادي ومصلحة الملاحظة والتربية في الوسط المفتوح بقمار
مذكرة ماستر علم الاجتماع تخصص علم اجتماع جريمة وانحراف
Keywords: جنوح الاحداث، السرقة، الأحداث الجانحين; Juvenile delinquency, theft, juvenile delinquents; Délinquance juvénile, vols, délinquants juvéniles